Trial of IMCI Algorithm in Disease Detection Card in Suku Anak Dalam in Batanghari District, Jambi - Izhar, M. Dody; Hubaybah, Hubaybah; Ruwayda, Ruwayda (KEMAS: Jurnal Kesehatan Masyarakat, 2020)
Integrated Management of Childhood Illness (IMCI) is one of management strategies for sick toddlers, in the form of curative and preventive efforts in order to overcome the toddler's health problems in the Suku Anak Dalam (SAD) in Jambi Province.The study uses a quasy experiment design. The research sample consisted of 11 parents of toddlers (1-5 years old) Tribe of Children in the Village of Hajran, Batin XXIV Sub-District, Batanghari District, Jambi. Statistical analysis with the significance level of the test p is <0.05.The results of the study revealed that the detection card for 1-5 year old children is a valid instrument (coeff: 0,564-0,814) and reliable (coeff: 0,765) in detecting the symptoms of the disease. Based on the analysis of paired samples T test it is known that there is a difference in knowledge before (= 6.45) with after (= 10.18) treatment, thus there is a significant influence (= 3.73. tTest= 5.632, pValue= 0.000) knowledge of parents.The study concluded that the detection card for diseases of infants is a valid and reliable instrument, and there was a significant effect of treatment with the IMCI algorithm.